Habitat Use of Migratory Shorebirds on the Coastline of Deli Serdang Regency, North Sumatra Province - Chairunas Adha Putra; Dyah Perwitasari-Farajallah; Yeni Aryati Mulyani (Bogor Agricultural University, Indonesia, 2017)
Mangrove forests an intertidal mudflat in the eastern coastal region of Deli Serdang are important habitats for migratory shorebirds. Land-use change and forest conversion threaten this important stopover point for migrating species. The lack of data and information of shorebirds habitats in this area limits conservation efforts and further threatens the survival of these species. The objective of this study is to investigate trends in habitat use by migratory shorebirds. Field work was conducted during migration season starting from October 2014 until April 2015. The presence of migratory shorebirds was assessed using binoculars and a monocular. Scan sampling was used to describe habitat use by shorebirds. The difference in behaviour among habitat was analyzed using analysis of variance. There were 30 species of shorebirds distributed across seven different habitat types in our study area. The most widely used habitat by shorebirds was mudflats, followed by marshes and plantations. This study revealed that mudflat habitat has high potential in supporting the existence of migratory shorebirds in this area.